BUSINESS EDUCATION GRADUATE ENTREPRENEURS’ RATING OF FINANCIAL MANAGEMENT AND INNOVATIVE THINKING SKILLS UTILIZATION IN ENTREPRENEURAL VENTURES IN NORTH CENTRAL STATES, NIGERIA (NAU Journal of Technology and Vocational Education, 2024)
The study investigated NCE business education graduate entrepreneurs’ ratings of financial management and innovative thinking skills utilization in entrepreneurial ventures in North Central States, Nigeria. The study which employed a descriptive survey identified two entrepreneurial skills which were financial management and innovative thinking skills. Two research questions and two hypotheses were formulated for the study. The entire registered 149 NCE business education graduate entrepreneurs operating in the North Central States, Nigeria constituted the population of the study. There was no sampling since the entire population was considered manageable. 30-item structured questionnaire titled Questionnaire onEntrepreneurs’ Rating of Entrepreneurial Skills Utilization in Entrepreneurship (QERESUE) was adopted for the study. The reliability of the instrument was ascertained using Pearson Product Moment Correlation Coefficient to obtain rcoefficient of 0.77 and 0.82, respectively for clusters B1and B2 of the questionnaire. The questionnaire was distributed to the 149 NCE business education graduate entrepreneurs in the North Central States, Nigeria. Four copies of the questionnaire were not returned and so 145 copies were used for the study. The research questions were analyzed using descriptive statistics of mean and standard deviation. t-test andANOVA were used to test the null hypotheses of the study at a 0.05 level ofsignificance. The findings of the study revealed that financial management skills were sometimes utilized in entrepreneurship, while Innovative thinking skills were often used. With respect to the findings, the following recommendations were put forward, among which was that institutional authorities in collaboration with the National Commission for Colleges of Education (NCCE) should, as a matter of policy institute regular training in entrepreneurial skills development for all teachers of business education to enable them acquire adequate knowledge of financial management skillsand innovative thinking skills so as to be in a better position to impact it effectively for optimal utilization.
Keywords: Skills, Entrepreneurship, Financial Management Skills, Innovative Thinking Skills